Restorative Justice Paradigm: Policy Problems and Practices in the Criminal Justice System in Pontianak City - Fadhil, Moh. (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
The paradigm shift from retributive justice to restorative justice has encouraged institutional awareness that restorative justice methods are alternatives that need to be strengthened both in terms of policy and practice. This has prompted law enforcement agencies to begin drafting and enforcing restorative justice policies in the criminal case settlement process. The purpose of this research is to analyze the working process of restorative justice policies through their implementation practices in each institution that focuses on various criminal justice institutions in Pontianak City. This study will describe the factors that influence the process of working in restorative justice by elaborating on the paradigm of law enforcement officers, policies at their institutions, and their experiences and practices. The method used is normative-empirical legal research as research on law enforcement in concreto. Although the paradigm of punishment has shifted towards a restorative paradigm, the findings in the field showed frequent obstacles. First, cross-sectoral regulatory factors that regulate restorative justice mechanisms with different mechanisms. Second, the weak integration of the criminal justice system as seen in practice between the Pontianak Police and the Pontianak District Attorney Office has not shown the integration of the criminal justice system in the corridor of enforcing the principle of functional differentiation. Third, the factor of criminal law policy is overcriminalistic so it is still overshadowed by the retributive and punitive colonial paradigm. Fourth, factor in the small period of time in the prosecutor's office due to tiered assessments within the structural corridors of leadership. Fifth, the legal culture factor of society is still mostly punitive. Keywords: Paradigm; Restorative Justice; Criminal Justice System